Nanotechnology in contemporary dentistry: a comprehensive review of current clinical applications, bioactive materials, and future perspectives - Ahmed, Murtada A.; Albuhiri, Samar M.; Alanazi, Manal M.; Albogami, Ameerah A.; Alharbi, Jawaher N.; Alruwaili, Eman A.; Shabeen, Maryam A. (International Journal Of Community Medicine And Public Health, 2026)
This review explores the transformative shift in dentistry from biopassive materials to bioactive nanotechnology, addressing critical challenges such as polymerization shrinkage, secondary caries, and mechanical failure. Through a systematic search of PubMed, Scopus, Cochrane, and Google Scholar (2015–2026), the study evaluates the mechanisms and clinical efficacy of bioactive glass (BAG), nanohydroxyapatite (nHA), and calcium-phosphate scaffolds. Findings indicate that these nanomaterials outperform traditional composites by enabling deep biomimetic remineralization, providing Power of Hydrogen (pH)-responsive ion release, and reducing polymerization stress by up to 37% through advanced fillers like nanoclay. In clinical practice, nanotechnology enhances the polishability and wear resistance of restoratives, optimizes osseointegration via nanofeatured implant surfaces, and improves endodontic sealing through nanoparticle-enhanced sealers. The review concludes that the integration of smart stimuli-responsive systems, Artificial Intelligence (AI), and three-dimensional (3D) bioprinting is transitioning the field from prosthetic replacement to full biological tooth regeneration, establishing nanotechnology as the cornerstone of personalized, regenerative oral healthcare.